Mycobacterium tuberculosis attenuates Macrophage responses through Pentose Phosphate Pathway activity - McGrath, John (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2025)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis, is adept at evading host immune defences and establishing chronic infections, particularly within macrophages. Central to its survival is its ability to reprogram host metabolism. This work explores the metabolic interactions between Mtb and host macrophages, focusing on the role of the pentose phosphate pathway (PPP) in modulating immune responses during infection. Here, we demonstrate that central to Mtb’s survival is its ability to reprogram host metabolism, notably rerouting central carbon metabolism towards PPP activity, which fosters a metabolic environment favourable for bacterial replication. Previous work within our group demonstrated that Mtb suppresses glycolytic activity in macrophages through upregulation of the anti-inflammatory microRNA miR-21, which targets the glycolytic enzyme PFK-m. This suppression reduces the production of IL-1β, a critical antimycobacterial cytokine. Now, we further characterise this immuno-evasive phenomenon as a means to regulate PPP-derived NO and subsequently target mitochondrial-based metabolism. NO is a soluble endogenous gas produced in macrophages by the activity of iNOS and proposed to have direct bactericidal activity. However, this model is poorly understood and moreover disputed in the context of Mtb infection of macrophages. This work alongside other recent studies challenges this perspective, suggesting that NO serves a more immune-modulatory than anti-microbial role, including the orchestration of metabolic reprogramming. Moreover, we identify glycogen as a crucial substrate for Mtb-driven PPP activity. During infection, macrophages mobilize glycogen stores to sustain PPP-derived NO production, which inhibits mitochondrial respiration and suppresses immune function. Blocking glycogenolysis decreased NO accumulation and IL-1β secretion, highlighting the importance of glycogen in maintaining Mtb's metabolic niche. Notably, chronic infection elevates NO levels, enhancing Mtb replication through a feedback loop between NO and PPP activity, further supported by glycogen breakdown. This suppresses mitochondrial metabolism, including oxidative phosphorylation (OXPHOS), through inhibition of key enzymes in the tricarboxylic acid (TCA) cycle and the accumulation of the metabolite itaconate, which further reduces IL-1β production and facilitates bacterial survival. Finally, we show that targeting PPP activity can enhance macrophage-mediated killing of Mtb. Inhibiting NADPH oxidase (Nox2), which regenerates the PPP cofactor NADP, restored mitochondrial function and OXPHOS activity, leading to increased IL-1β production and bacterial clearance. These findings suggest that targeting metabolic pathways like the PPP offers a promising therapeutic strategy for boosting host immunity against tuberculosis.
APPROVED
Keywords: Mycobacterium tuberculosis; Macrophage; Pentose Phosphate Pathway; Metabolism